2007
DOI: 10.1002/jcb.21254
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of growth and cancer‐induced angiogenesis of aggressive human breast cancer cells (MDA‐MB‐231) on the chorioallantoic membrane of developing chicken embryos by E‐peptide of pro‐IGF‐I

Abstract: E-peptide of the pro-Insulin-like growth factor-I (pro-IGF-I) is produced from pre-pro-IGF-I by proteolytic cleavage in the post-translational processing. Previous in vitro studies conducted in our laboratory showed that Ea4-peptide of rainbow trout (rt) pro-IGF-I or Eb-peptide of human (h) pro-IGF-I exhibited activities including induction of morphological differentiation, inhibition of anchorage-independent cell growth and suppression of invasion of several well established human cancer cell lines such as MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…These results are consistent with those reported in mammals (Siegfried et al, 1992;Matheny et al, 2010;Yang and Goldspink 2002). Further studies conducted in our laboratory showed that both recombinant rtEa4-or synthetic hEbpeptide exerted unexpected anti-cancer cell activities in established human cancer cell lines such as MDA-MB-231, HT-29, HepG2, SK-N-F1, SKOV-3A, PC-3 and OVCAR-3B (Chen et al, , 2007Kuo and Chen 2002). These activities include: (i) induction of morphological differentiation and inhibition of anchorage-independent growth, (ii) inhibition of invasion and metastasis, and (iii) inhibition of cancer-induced angiogenesis.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those reported in mammals (Siegfried et al, 1992;Matheny et al, 2010;Yang and Goldspink 2002). Further studies conducted in our laboratory showed that both recombinant rtEa4-or synthetic hEbpeptide exerted unexpected anti-cancer cell activities in established human cancer cell lines such as MDA-MB-231, HT-29, HepG2, SK-N-F1, SKOV-3A, PC-3 and OVCAR-3B (Chen et al, , 2007Kuo and Chen 2002). These activities include: (i) induction of morphological differentiation and inhibition of anchorage-independent growth, (ii) inhibition of invasion and metastasis, and (iii) inhibition of cancer-induced angiogenesis.…”
supporting
confidence: 91%
“…Recombinant rtEa4-peptide, hEb-peptide and control protein were prepared following the method described by our laboratory (Tian et al, 1999;Kuo and Chen, 2002;Chen et al, 2007). Briefly, E. coli cells, transformed with an expressing vector pET-15b (Novagen, EMD Chemicals, Gibbstown, NJ) containing the coding sequence of rtEa4-peptide or hEb-peptide, were cultured in 5 ml of LB broth for 4 h, diluted to 500 ml LB broth and allow the culture to grow at 37 o C. The culture was induced with 1 mM isopropyl β-D-thiolactopyranoside (IPTG) at an OD 600 of 0.6-0.8 for 2 h. Induced cells were harvested by low speed centrifugation and resuspended in 10 ml of a binding buffer (50 mM imidazole, 0.5 M NaCl, 20 mM Tris-HCl, pH 7.9).…”
Section: Preparation Of Rtea4-and Heb-peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of IGFs produced reflects the type of epithelial cells and the type of cellular growth (45). Various transcripts and variable IGF-1 precursor peptides act, first of all, as mitogenic factors but they may also inhibit the growth of neoplastic cells (17,18,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Peptide Ea which is composed of 35 amino acids is spliced out from the C terminal region of premature IGF-1 (i.e., pre-protein). It may be responsible for both mitogenic (26) and inhibitory effects on cancer cell growth (27). Furthermore, peptide Eb, which is composed of Eb1 and Eb2 peptides may exert mitogenic effects on IGF-1 independently; however, the activity of both peptides differs in various types of tissue (28).…”
Section: Differential Expression Of Igf-1 Mrna Isoforms In Colorectalmentioning
confidence: 99%